British exports and exchange restrictions abroad - Swiss Bank Corporation (London : Swiss Bank Corporation, 1961)
This is a handbook that indicates the principal regulations affecting the British exporter. It also highlights the expanding United Kingdom exports to other countries.
usc 21/09/18
Loans
Keywords: Commercial policy; Foreign exchange; Foreign exchange--Law and legislation; Exchange; Import quotas; Great Britain